2004
DOI: 10.1182/blood-2003-10-3735
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-leukemia in a retrovirally induced murine CML model: mechanisms of T-cell killing

Abstract: The graft-versus-leukemia (GVL) effect, mediated by donor T cells, has revolutionized the treatment of leukemia. However, effective GVL remains difficult to separate from graft-versus-host disease (GVHD), and many neoplasms are GVL resistant. Murine studies aimed at solving these problems have been limited by the use of leukemia cell lines with limited homology to human leukemias and by the absence of loss-of-function leukemia variants. To address these concerns, we developed a GVL model against murine chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 88 publications
3
58
0
Order By: Relevance
“…Retroviral supernatants were generated by transfection of the Plat-E retrovirus packing cell line as described previously (28,29,31,32). p210-infected bone marrow progenitors were generated as described previously (28,29,32). Briefly, B6 mice were injected on day Ϫ6 with 5 mg of 5-fluorouracil (Pharmacia & Upjohn).…”
Section: Retrovirus Production and Progenitor Infectionsmentioning
confidence: 99%
“…Retroviral supernatants were generated by transfection of the Plat-E retrovirus packing cell line as described previously (28,29,31,32). p210-infected bone marrow progenitors were generated as described previously (28,29,32). Briefly, B6 mice were injected on day Ϫ6 with 5 mg of 5-fluorouracil (Pharmacia & Upjohn).…”
Section: Retrovirus Production and Progenitor Infectionsmentioning
confidence: 99%
“…Retroviral supernatants were generated by transfection of Plat-E retrovirus packing cell line 16 as described. [17][18][19] Progenitor infections p210-infected progenitors were generated as previously described. 13,17,19 Briefly, B6 mice were injected on day Ϫ6 with 5 mg 5-fluorouracil (Pharmacia & Upjohn, Kalamazoo, MI).…”
Section: Retrovirus Productionmentioning
confidence: 99%
“…[17][18][19] Progenitor infections p210-infected progenitors were generated as previously described. 13,17,19 Briefly, B6 mice were injected on day Ϫ6 with 5 mg 5-fluorouracil (Pharmacia & Upjohn, Kalamazoo, MI). On day Ϫ2, BM cells were harvested and cultured in prestimulation media (Dulbecco modified Eagle medium, 15% fetal bovine serum, interleukin-3 (6 ng/mL), interleukin-6 (10 ng/mL), and stem-cell factor (10 ng/mL; all cytokines from PeproTech; Rocky Hill, NJ).…”
Section: Retrovirus Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have shown that larger numbers of lymphocytes can facilitate engraftment [39,40] and produce a greater GVL effect [41]. Consequently, we tested higher doses of TK + TC.…”
Section: Determination Of An Mtd Of Hsv-tk + Lymphocytesmentioning
confidence: 99%